Étude sur l’influence du « chercheur-apprenant » dans des recherches collectives en éducation - Jean-Michel Perez (Questions Vives, 2022)
In the context of education, more and more international and national reports are encouraging the development of collaborative research. But if this approach can be perceived as a promising way of scientific legitimisation for researchers (C) or as places of answers to professional questions that teachers (E) may ask themselves, works are also interested in their limits. In this article, the aim is firstly to enable the reader to identify the reference framework which, based on the conceptual irrigation of Rogers (1942), Ferry (1971), Douglas (1986/1999), Chevallard (1992), underpins a conception of the practice of group work between E- and C- teachers when there is an intention to produce knowledge and uses about education and inclusive practices (Perez, 2018). It then looks at some of the obstacles to this conception: the illusion of liberation from anxiety, the illusion of grasping the object, or the illusion of an equal relationship between the C and the E. Informed by this knowledge, a final section looks at the ethics of accompanying the researcher in a device with a transformative aim.